Influence of neutron irradiation on elctrooptical and structural properties of silicon - Groza, A.A.; Venger, E.F.; Varnina, V.I.; Holiney, R.Yu.; Litovchenko, P.G.; Matveeva, L.A.; Litovchenko, A.P.; Sugakov, V.I.; Shmatko, G.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Processes of structure defects formation, which accompanied by oxygen precipitation after a neutron irradiation (10¹⁵- 10¹⁹ n/cm²) and high-temperature treatment (800 - 1000°С) in CZ silicon, were investigated by the transmission electron microscopy. Influence of the structure defects on electrooptical properties of silicon was revealed.